Rozliczenia budżetowe między Polską a Unią Europejską w sektorze rolno-żywnościowym jako przesłanka poprawy jego konkurencyjności po 2004 roku - Czyżewski, Andrzej (Budgetary Accounts Between Poland and European Union in the Agri-Food Sector as the Circumstance of the Turn of Its Competitiveness after 2004 Year, 2006)
The purpose of the matter under discussion is the analysis of the budgetary acts after the integration with the European Union, in the years 2004-2006 in order to estimate the size and structure of budgetary accounts between Poland and EU. Now it is proved that financial condition of this sector was changed for a short time before the accession of Poland with the European Union (2003-2004). Expenses' participation of agriculture, development of rural area and agricultural markets in the light of all budgetary expenses increases substantially, which can include to positive circumstance for the turn of agricultural policy in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 153-158